Development and validation of a prognostic nomogram for gallbladder papillary adenocarcinoma - Wang, Zhenfeng; Wang, Longlong; Hua, Yunqi; Zhuang, Xiang; Bai, Yu; Wang, Huming (Frontiers in Oncology, 2023)
Background Gallbladder papillary adenocarcinoma (GBPA) is an uncharacteristically gallbladder cancer. Although some studies have shown that the prognosis of GBPA patients is significantly better than that of gallbladder adenocarcinoma(GBA) and gallbladder mucinous adenocarcinoma (GBMA) due to its rarity, there is a lack of large sample studies necessary to confirm the clinical characteristics and survival rate of GBPA. Therefore, this study aimed to describe the clinicopathological characteristics affecting survival in GBPA. This data was then used to establish a prognostic nomogram for GBPA. Methods The data of patients diagnosed with gallbladder cancer between 2004 to 2015 were extracted from the SEER database. The clinical features and survival of patients with GBPA were compared with those of GBA and GBMA after being matched by PSM to balance the baseline. To investigate the GBPA prognostic factors, Cox proportional hazard analysis were conducted. In order to forecast the prognosis of GBPA, the OS and CSS nomograms were created. The performance and discrimination of the nomogram were measured using C-index, calibration curves, ROC,and DCA was applied to examine the net benefit of nomograms compared with the TNM staging system. Results A total number of 6302 patients were enrolled, including 281 patients with GBPA, 5798 patients with GBA, and 223 patients with GBMA. The PSM analysis showed a differ statistically significantly in the OS between GBPA and GBA. However, there has no statistically difference in CSS. Conversely, the OS and CSS between GBPA and GBMA have statistically significant differences. Age, marital, T stage, and M stage were strongly linked to the prognosis for OS, while T-stage, M-stage, and surgery were significantly associated with the prognosis for CSS in GBPA patients. The C-indices for the OS and CSS nomograms were 0.701 and 0.651, respectively. The calibration curves showed that the nomograms were well consistency. The DCA showed that compared with the TNM system, the nomogram models had a significant positive net benefit in survival prediction. Conclusion GBPA has special clinical features and survival outcomes in contrast to other gallbladder carcinomas. Nomograms constructed were provided a better prediction of survival for GBPA patients than the traditional TNM models.